Synthesis of stimuli-sensitive copolymers by RAFT polymerization : potential candidates as drug delivery systems - Tebaldi, Marli Luiza (2014)
Poly(2-(dimethylamino)ethylmethacrylate-b-methymethacrylate) (PDMAEMA-b-PMMA) poly(2- (dimethylamino)ethylmethacrylate-b-vinylcaprolactam-b-(2-(dimethylamino)ethyl methacrylate) (PDMAEMA-b-PVCL-b-PDMAEMA) and poly(vinylcaprolactam-b-(2-(dimethylamino) ethylmethacrylate-b-vinylcaprolactam) (PVCL-b-PDMAEMA-b-PVCL) block copolymers were obtained by reversible addition-fragmentation chain transfer (RAFT) polymerization, and the effect of the solution pH on the particle size was investigated. In the case of PDMAEMA-b-PMMA, PDMAEMA was first synthesized using 2-cyanoprop-2-yl dithiobenzoate (CPDB) as a chain transfer agent (CTA), which was subsequently used for the RAFT polymerization of MMA. The triblock copolymers were obtained using PDMAEMA or PVCL as macro-CTAs prepared using dibenzyl trithiocarbonate (DBTTC) as a bifunctional RAFT agent. The structure and formation of the copolymers was confirmed through 1H NMR and SEC analysis. The particle size varied considerably depending on the pH of the aqueous solutions of copolymers indicating that these materials could be potential candidates for biomedical applications.